INFLUENCE OF REDOX BUFFERS AND THE COMPOSITION OF NATURAL WATERS ON THE MIGRATION OF URANIUM AND PLUTONIUM ACCOMPANYING THE DISPOSAL OF SPENT NUCLEAR FUEL - Gaskova O.L. (My University, 2006)
A thermodynamic model is proposed for the description of U and Pu behavior during their possible leaching from SNF in contact with underground waters. The model is based on the available information on the technology of long-term storage of RAW in geologic environments, the test results obtained in planned and operating disposal sites, and experimental data on the solubility of irradiated U and Pu phases. Water-rock interactions were calculated using the actual compositions of the buffers aimed at suppressing actinide removal from the radiolysis zone and natural ground waters in equilibrium with various rocks. It was supposed that the use of model concentrations in two equilibrium phases for the calculation of distribution coefficients (immobilization if Kdis = M solid/M sq) provides a fundamental significance to the calculations and may help in the development of predictive models. © Pleiades Publishing, Inc. 2006.